Herbivore-Associated Bacteria as Potential Mediators and Modifiers of Induced Plant Defense Against Spider Mites and Thrips - Schausberger, Peter (Frontiers in Plant Science, 2018)
Induced plant defense, comprising contact with exogenous stimuli, production of endogenous signals alerting the plant, associated biochemical cascades, and local and/or systemic expression of the defense mechanisms, critically depends on the nature of the inducing agents. At large, bio-trophic pathogenic microorganisms and viruses usually trigger the salicylate (SA)-mediated pathway, whereas necro-trophic pathogens and herbivores usually trigger the jasmonate (JA)-mediated pathway in plants. The SA- and JA-mediated pathways do not operate independently but commonly interfere with each other. Several recent studies revealed abnormal plant responses upon herbivore attack in diverse plant-herbivore systems. Observed abnormalities range from suppression of the common JA-pathway, induction of the SA-pathway to no response, yet the underlying proximate causes and ultimate consequences of these variations are elusive. Strikingly, some studies provide compelling evidence that anti-herbivore plant responses may decisively depend on bacteria associated with the herbivore attacking the plant (HABs for herbivore-associated bacteria). HABs may influence herbivore recognition by the plant and alter the biochemical cascades inside plants. Here, I report cases in point of HABs manipulating induced anti-herbivore plant responses, suggest spatial and temporal categorization of HABs, and point at proximate and ultimate aspects of plant defense manipulation by HABs. Following, I overview the diversity of HABs of spider mites and herbivorous thrips, argue that, considering recently reported phenomena of abnormal plant responses upon spider mite attack, some of these HABs could represent important, but hitherto largely neglected, mediators/modifiers of induced plant defense against spider mites and thrips, and conclude with suggestions for future research.